2013
DOI: 10.1620/tjem.231.145
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphate Transporters Ameliorates the Inflammatory and Necrotic Side Effects of the Nitrogen-Containing Bisphosphonate Zoledronate in Mice

Abstract: Bisphosphonates (BPs) are pyrophosphate analogs. They are widely used against enhanced boneresorption in various diseases. Nitrogen-containing BPs (N-BPs) exhibit strong anti-bone-resorptive effects but have inflammatory and necrotic side effects. The non-nitrogen-containing BPs (non-N-BPs) etidronate and clodronate lack such side effects, but their anti-bone-resorptive effects are weak. In mice, etidronate and clodronate reduce the inflammatory/necrotic effects of N-BPs, even those of zoledronate, the N-BP wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…10) Here, we compared the effects of 50 mM PFA, Eti, and Clo on the inflammatory effects of other N-BPs. As shown in Fig.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…10) Here, we compared the effects of 50 mM PFA, Eti, and Clo on the inflammatory effects of other N-BPs. As shown in Fig.…”
Section: )mentioning
confidence: 99%
“…8,9) Concerning the mechanism underlying such interesting effects of Eti and Clo, our pharmacological studies have suggested that they can competitively inhibit the entry of N-BPs into soft-tissue cells, and that this possibly occurs via SLC20 and/or SLC34 phosphate transporters. 10) Tiludronate (Til, not used in Japan) is a cyclic non-N-BP. Thus, it might be expected that tiludronate would be an effective inhibitor of the entry of cyclic N-BPs into softtissue cells, thereby reducing or preventing their inflammatory side effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these phosphate transporter families, SLC20 and/or SLC34 have been suggested to be involved in the transport of N-BPs. 16) Among the antibodies that would be required to detect them by immunostaining, antibodies against only SLC20a1 and SLC20a2 are commercially available. Figure 9 shows immunostaining results obtained using those two antibodies.…”
Section: Detection Of Phosphate Transporters Within Ear-pinnasmentioning
confidence: 99%
“…It should be noted that such cytotoxic effects of N-BPs are initiated by their entry into soft-tissue cells, 12) and that there are few reports of inflammatory/necrotic side effects in patients treated with non-N-BPs. 10) Indeed, the non-N-BPs etidronate and clodronate almost completely lack inflammatory and necrotic effects in mice, 7,16) and they are hardly retained at all within soft-tissues in mice after intravenous injection.…”
Section: Discussionmentioning
confidence: 99%